Potential of traditional Chilean blood-fleshed peach to support livelihood opportunities in local agriculture - Marchant, Lorena; Campos, Javiera; Luco, Javiera; Ramirez, Cesar; Barrientos, Freddy; Carrasco, Basilio; Silva, Herman (Frontiers in Sustainable Food Systems, 2022)
The blood-flesh peach or vineyard peach is an older heritage cultivar with juicy red-flesh and tart-sweet flavor. They are popular in France, where more than 200 years ago wine growers used to plant them on the vineyards as biological markers to detect the presence of powdery mildew. It is present in countries such as China, Italy, New Zealand, Australia and USA however, it remains a very rare variety worldwide. In Chile, the blood-flesh peach has a centenary presence in rural orchards where is called “Durazno Betarraga.” Reproduced by seeds, it has pass through generations of family farmers and has been adapted to local environmental conditions. This red-flesh peach is a local variety considered part of their traditional diets, however, cultural changes in food consumption, short postharvest life and water scarcity due to climate change are threatening its conservation. One of the objectives of the International Year of Fruits and Vegetables, as defined by the FAO, is to integrate small holders and family farmers into value chains for sustainable production and consumption of fruits and vegetables recognizing the contributions of farmer's landraces to their food security, nutrition, livelihoods and income. To promote this objective, we present the work we have been carry out for several years with a farming community. We have conducted ethnographic research to provide a qualitative description of the agricultural value of the blood peach in a limited territory of the Maule Region defined as the study area. For the quantitative section of our research we analyzed the antioxidant capacity (ORAC) and total polyphenol content and compared them with those of other fruits. To gather information on the presence of the blood-fleshed peach in other regions of Chile, we used a citizen science approach through social networks. We propose that this local variety is an innovative raw material to develop healthy fruit-based food, thus encouraging its conservation and consumption with a positive social and economic impact for the community and the local food system.